Postmodernity and fin de siècle in Uruguay - Hugo Achugar (Studies in 20th & 21st Century Literature, 1990)
Since the end of the military regime, Uruguay has been culturally and politically divided. During the period of repression, the opposition was united against the dictatorship. Yet economic decline and the military dictatorship have profoundly divided Uruguayan culture. On the positive side, new cultural actors have emerged—women, younger poets and writers and the marginalized—on the negative side, there is a sense of malaise that has neither been adequately discussed nor theoretized.
Keywords: fin de siècle; military regime; politics; culture; Uruguay; Uruguayan literature; repression; opposition; dictatorship; women; young poets; writers; marginalized